Afadin is a scaffold protein repressing insulin action via HDAC6 in adipose tissue. (2nd July 2019) - Lundh, Morten; Petersen, Patricia SS; Isidor, Marie S; Kazoka‐Sørensen, Dolly NM; Plucińska, Kaja; Shamsi, Farnaz; Ørskov, Cathrine; Tozzi, Marco; Brown, Erin L; Andersen, Emil; Ma, Tao; Müller, Ulrich; et al.
Abstract: Insulin orchestrates metabolic homeostasis through a complex signaling network for which the precise mechanisms controlling its fine‐tuning are not completely understood. Here, we report that Afadin, a scaffold protein, is phosphorylated on S1795 (S1718 in humans) in response to insulin in adipocytes, and this phosphorylation is impaired with obesity and insulin resistance. In turn, loss of Afadin enhances the response to insulin in adipose tissues via upregulation of the insulin receptor protein levels. This happens in a cell‐autonomous and phosphorylation‐dependent manner. Insulin‐stimulated Afadin‐S1795 phosphorylation modulates Afadin binding with interaction partners in adipocytes, among which HDAC6 preferentially interacts with phosphorylated Afadin and acts as a key intermediate to suppress insulin receptor protein levels. Adipose tissue‐specific Afadin depletion protects against insulin resistance and improves glucose homeostasis in diet‐induced obese mice, independently of adiposity. Altogether, we uncover a novel insulin‐induced cellular feedback mechanism governed by the interaction of Afadin with HDAC6 to negatively control insulin action in adipocytes, which may offer new strategies to alleviate insulin resistance. Synopsis: The scaffold protein Afadin dampens insulin action in adipocytes and impairs adipose tissue function by a negative feedback mechanism involving Afadin phosphorylation, recruitment of HDAC6 and suppression of the insulin signaling pathway. Afadin is phosphorylated at serine 1795 in response to insulin and this phosphorylation is impaired in obese and insulin resistant conditions. Afadin phosphorylation suppresses insulin action by recruiting HDAC6 and reducing insulin receptor levels. Depletion of Afadin in adipose tissues improves metabolic health in diet‐induced obese mice. Abstract : The scaffold protein Afadin dampens insulin action in adipocytes and impairs adipose tissue function by a negative feedback mechanism involving Afadin phosphorylation, recruitment of HDAC6 and suppression of the insulin signaling pathway.